Is diet a determining factor in the induction of gingival inflammation by dental plaque?: A secondary analysis of clinical studies - Wölber, Johan; Bartha, Valentin; Baumgartner, Stefan; Tennert, Christian; Schlagenhauf, Ulrich; Ratka-Krüger, Petra; Vach, Kirstin (Nutrients, 2024)
The aim was to determine the association between plaque and gingival inflammation reported by dietary interventions. Data of four clinical studies dealing with changed nutrition and gingival examination were reanalyzed with regard to gingival inflammation (GI), plaque (PI), and bleeding on probing (BOP). Dietary changes basically involved avoiding sugar, white flour and sweetened drinks and focusing on whole foods for 4 weeks. The control groups were to maintain their usual diet. All participants had to reduce their oral hygiene efforts. Linear regression models taking the clustering of the data due to several studies into account were applied. In total, data of 92 participants (control groups: 39, test-groups 53) were reanalyzed. While both groups showed a slight increase in dental plaque, only the test groups showed a significant decrease in inflammatory parameters: GI (mean value difference End-Baseline (Δ): −0.31 (±SD 0.36)) and BOP (Δ: −15.39% (±16.07)), both p < 0.001. In the control groups, there was a constant relation between PI and GI, while the experimental group showed a decreasing relationship in GI/PI (p = 0.016), and even an inverted relationship BOP/PI under a changed diet (p = 0.031). In conclusion, diet seems to be a determining factor how the gingiva reacts towards dental plaque.